Adversity quotient among students at traditional moslem school - Suheri; Setyosari, Punaji; Utaya, Sugeng; Djatmika RW, Ery Tri (Kasetsart Journal of Social Sciences, 2021)
This study aims to measure the demographic influence of student variables on Adversity Quotient (AQ). The research analyzed the relationship and Adversity Quotient in studying students at Islamic Boarding Schools in East Java, Indonesia. The Adversity Quotient research questionnaire used an instrument made by Stolz, while the independent variables included gender, age, learning achievement, regional origin, parental education level, previous educational background. The findings of this study indicate that the Adversity Quotient was formed by two factors, namely, internal factors consisting of gender, age, education, duration of study and external factors, which are formed by environmental factors, while the family environment does not have a significant effect on AQ. The contribution of education in forming Adversity Quotient students consists of student learning experiences in training fighting power, strengthening mental aspect or character and performance of independent students. While Achievement does not directly form Adversity Quotient, and students who have high cognitive abilities do not necessarily have higher AQ, because cognitive abilities are more examples of conceptual problems and case studies are less precise.